Nonlinearity of the frequency-temperature characteristics of LC-cut quartz resonators - ŻUCHOWSKI, E.; ŁYSAKOWSKA, M. (Archives of Acoustics, 1991)
On the basis of the classical theory of thickness vibrations, the formulas for the temperature coefficients and their angular derivatives of the frequency-temperature characteristics of quartz resonators with LC-cut are derived. Approximation of these characteristics by straight lines enables the evaluation of nonlinearity effects in a given range of temperature. A practical example is given.